Analisis Penyusunan Anggaran Berbasis Kinerja dan Realisasi Anggaran pada Badan Pengelolaan Keuangan dan Asset Daerah Pemerintahan Kota Medan - Jukhairia Ritonga; Nurlaila Nurlaila (VISA: Journal of Vision and Ideas, 2023)
The purpose of this study is the realization of the budget based on the performance and analysis of the budget report at the Regional Financial and Asset Management Agency of the Medan City Government during the 2020-2021 fiscal year. The application of the method in this research is descriptive qualitative, by collecting data through interviews and observations. Based on the research conducted, it was found that there was an influence of the budget with the realized budget, and this became quite appropriate for the Medan City Government BPKAD, so that it became a natural thing if there were funds that had not been delivered to be realized due to the pandemic period that was hitting Indonesia. Keywords: Budgeting, Budget Realization